2017
DOI: 10.2527/jas.2016.1345
|View full text |Cite
|
Sign up to set email alerts
|

Further testing of Melatonin Receptor 1a for out-of-season reproduction in the Cornell flock and allelic frequencies compared with Romney sheep12

Abstract: Sheep are seasonally polyestrous breeders, meaning they breed when day length shortens in the autumn. Ewes respond to changing day length through chemical pathways involving melatonin receptors. Some breeds, such as Dorset, are known to be less seasonal with many ewes able to breed and lamb year-round. The Melatonin Receptor 1a () gene was identified as a candidate gene controlling out-of-season lambing. The first studies in the Cornell STAR accelerated lambing flock found that a allele was associated with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, melatonin receptor subtype MTNR1A was not found to be expressed in kisspeptin neurons but MTNR1A was found in the ovine pars tuberalis to regulate prolactin, which has indirect effects on kisspeptin [ 204 ]. MTNR1A polymorphisms showed no significant relationship to “out-of-season lambing” [ 205 ]. When melatonin binds particular subtype receptors sheep, subsequent molecular and physiological responses are yet to be distinguished.…”
Section: Melatonin Signalling In Reproductionmentioning
confidence: 99%
“…However, melatonin receptor subtype MTNR1A was not found to be expressed in kisspeptin neurons but MTNR1A was found in the ovine pars tuberalis to regulate prolactin, which has indirect effects on kisspeptin [ 204 ]. MTNR1A polymorphisms showed no significant relationship to “out-of-season lambing” [ 205 ]. When melatonin binds particular subtype receptors sheep, subsequent molecular and physiological responses are yet to be distinguished.…”
Section: Melatonin Signalling In Reproductionmentioning
confidence: 99%
“…Small Tail Han sheep, a local sheep breed in China, is characterized by high productivity and year‐round oestrus (Liu, Jiang, & Du, 2003), and the breed has been considered as a good source of ovine reproductive genes in China. In the early studies, studies reported that the relationship between polymorphism of MTNR1A and litter size and reproductive seasonality traits in different breeds of ruminants (Gunwant et al., 2018), such as sheep (Calvo et al., 2018; Chu et al., 2006, 2008; Mateescu, Lunsford, & Thonney, 2009; Notter et al, 2003; Pelletier et al., 2000; Posbergh, Murphy, & Thonney, 2017), goat (Abdolahi, Shokrollahi, Saadati, & Morammazi, 2019; Chu et al., 2007; Hua, 2006) and water buffalo (Gunwant et al., 2018). However, there are few reports about MTNR1B .…”
Section: Introductionmentioning
confidence: 99%